Flip the funnel how to use existing customers to gain new ones - Jaffe, Joseph 1970- (Wiley, 2010)
"If there's anything the recession of 2009 taught us, it was the importance of investing in our customers, but when was this any different? So says Joseph Jaffe, bestselling author of Life After the 30-Second Spot and Join the Conversation, and a leading expert and thought leader on new media and social media. In most businesses, it costs roughly five-to-ten times more to acquire a new customer than it does to retain an existing one, and yet companies continue to disproportionately spend their budgets into the "wrong" end of the funnel <U+2013> the mass media or awareness side. What we haven't paid enough attention to is the "right" end of the funnel-the word-of-mouth component that essentially acts as a multiplier for future business. The economic impact of an active, engaged and loyal customer is tremendous. And the same is true of the opposite scenario, namely the impact of angry customers and negative word-of-mouth or referrals. It is this thinking that Jaffe has channeled to challenge marketers to "flip the funnel" once and for all. With a renewed focus and energy on customer experience, it is possible to grow your sales, while decreasing your budget <U+2013> in other words, getting more from less. Engaging a few customers to spread the word to many. Using this new "flipped funnel" model, together with a set of new rules of customer service and a revolutionary customer referral and activation process, you'll learn how to transform your existing customers into your best salespeople. In addition, Jaffe will explain how to best introduce and combine both digital and social media tools to boost your loyalty arsenal, deploy "influencer marketing" and implement word-of-mouth strategies that inspire your loyal, opinionated, and most vocal customers to become credible, persuasive, and influential endorsers of your products and services." -- from publisher's website.